Tính a) (2x-y+2)^2 b)(xy/2-x/3).(xy/2+x/3) ko lm tắt nha

Question

Tính a) (2x-y+2)^2
b)(xy/2-x/3).(xy/2+x/3) ko lm tắt nha

in progress 0
Eloise 4 tháng 2021-08-25T15:03:28+00:00 2 Answers 9 views 0

Answers ( )

    0
    2021-08-25T15:04:46+00:00

    a,

    $(2x-y+2)^2$

    $= (2x-y+2)(2x-y+2)$

    $= 4x^2-2xy+4x-2xy+y^2-2y+4x-2y+4$

    $= 4x^2+y^2-4xy+8x-4y+4$

    b,

    $(\dfrac{xy}{2}-\dfrac{x}{3})(\dfrac{xy}{2}+\dfrac{x}{3})$

    $=(\dfrac{xy}{2})^2-(\dfrac{x}{3})^2$

    $=\dfrac{x^2y^2}{4}-\dfrac{x^2}{9}$

    0
    2021-08-25T15:05:23+00:00

    a) $(2x-y+2)^2$

    $=(2x-y+2).(2x-y+2)$

    $=[(2x-y+2).2x]-[(2x-y+2).y]+[(2x-y+2).2]$

    $=[4x^2-2xy+4x]-[2xy-y^2+2y]+[4x-2y+4]$

    $=4x^2-2xy+4x-2xy+y^2-2y+4x-2y+4$

    $=4x^2+y^2+(-2xy-2xy)+(4x+4x)+(-2y-2y)+4$

    $=4x^2+y^2-4xy+8x-4y+4$

    b) $(\dfrac{xy}{2}-\dfrac{x}{3})(\dfrac{xy}{2}+\dfrac{x}{3})$

    $=[(\dfrac{xy}{2}-\dfrac{x}{3}).\dfrac{xy}{2}]+[(\dfrac{xy}{2}-\dfrac{x}{3}).\dfrac{x}{3}]$

    $=[\dfrac{x^2y^2}{4}-\dfrac{x^2y}{6}]+[\dfrac{x^2y}{6}-\dfrac{x^2}{9}]$

    $=\dfrac{x^2y^2}{4}-\dfrac{x^2y}{6}+\dfrac{x^2y}{6}-\dfrac{x^2}{9}$

    $=\dfrac{x^2y^2}{4}+(-\dfrac{x^2}{y}+\dfrac{x^2y}{6})-\dfrac{x^2}{9}$

    $=\dfrac{x^2y^2}{4}-\dfrac{x^2}{9}$

     

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )